Sarcopenia as potential biological substrate of long COVID‐19 syndrome: prevalence, clinical features, and risk factors. Issue 4 (14th June 2022) - Martone, Anna Maria; Tosato, Matteo; Ciciarello, Francesca; Galluzzo, Vincenzo; Zazzara, Maria Beatrice; Pais, Cristina; Savera, Giulia; Calvani, Riccardo; Marzetti, Emanuele; Robles, Maria Camprubi; Ramirez, Maria; Landi, Francesco; et al.
Abstract: Background: Severe clinical pictures and sequelae of COVID‐19 disease are immune mediated and characterized by a 'cytokine storm'. Skeletal muscle has emerged as a potent regulator of immune system function. The aim of the present study is to define the prevalence of sarcopenia among COVID‐19 survivors and the negative impact of sarcopenia on the post‐acute COVID‐19 syndrome and its related risk factors. Methods: A total of 541 subjects recovered from COVID‐19 disease were enrolled in the Gemelli Against COVID‐19 Post‐Acute Care between April 2020 and February 2021. They underwent a multidisciplinary clinical evaluation and muscle strength and physical performance assessment. Results: Mean age was 53.1 years (SD 15.2, range from 18 to 86 years), and 274 (51%) were women. The prevalence of sarcopenia was 19.5%, and it was higher in patients with a longer hospital stay and lower in patients who were more physically active and had higher levels of serum albumin. Patients with sarcopenia had a higher number of persistent symptoms than non‐sarcopenic patients (3.8 ± 2.9 vs. 3.2 ± 2.8, respectively; P = 0.06), in particular fatigue, dyspnoea, and joint pain. Conclusions: Sarcopenia identified according to the EWGSOP2 criteria is high in patients recovered from COVID‐19 acute illness, particularly in those who had experienced the worst clinical picture reporting the persistence of fatigue and dyspnoea. Our data suggest that sarcopenia, through the persistence of inflammation, could be the biological substrate of long COVID‐19 syndrome. Physical activity, especially if associated with adequate nutrition, seems to be an important protective factor.